PROBABILITY OF DEFAULT MEASUREMENT MODELS OF MERTON ON SHARIAH BANKS AND CONVENTIONAL BANKS IN INDONESIA FOR 2011-2017 PERIOD - Silvira, Okta; Rani, Lina Nugraha (Jurnal Syariah, 2021)
This paper provides empirical evidence of the comparison default risk in Islamic banks and conventional banks in Indonesia over the 2011 to 2017 period. The calculation of bank default risk using a Merton Model has allowed the measure of the Distance-to-Default (DD) and Default probability (DP). This study was extended to investigate the differences of bank default risk between Islamic banks and conventional banks with the employ of T-test. The evidence shows Islamic banks as banks that are far from the Possibility of Default Risk rather than conventional banks. The T-test indicates that there are significant differences in the Probability of Default values between Islamic banks and conventional banks. These findings could be relevance to regulators in Indonesia to support the growth of Islamic, which helps in maintaining financial system stability and avoiding systemic risk.